Khulu: Tinjauan Menurut Hadits Bukhori Dan Pasal 148 KHI - Faza Pauzia Hermawan; Tajul Arifin (LP3M INSTITUT KH YAZID KARIMULLAH, 2024)
Divorce is a social phenomenon that is quite complex and has various negative impacts for the person concerned, both for husband and wife as well as for children and families. Khulu is a method of divorce in Islam, where the party who proposes to dissolve the marriage bond is the wife. This journal discusses how khulu is regulated in Islam as contained in Bukhori's hadith and is reviewed or compared with how khulu is regulated in the Compilation of Islamic Law article 148. This research aims to analyze iwadh khulu according to Bukhori's hadith and Article 148 of the Compilation of Islamic Law (KHI) in Indonesia. Based on the research results, there is a discrepancy in the amount of iwadh based on the perspective of the Bukhari Hadith and the Compilation of Islamic Law Article 148. There needs to be a re-examination regarding this because the khulu' that occurred in the past and now have quite different causes. In contemporary cases, khulu often occurs as a result of poverty, the lack of physical and spiritual support. Iwadh based on the Bukhari Hadith is the return of the dowry received by the wife. Meanwhile, in the Compilation of Islamic Law, the amount of iwadh is the result of an agreement between husband and wife..